NComputing Adoption: Issues and Challenges - Esmael V. Maliberan (JOIV : International Journal on Informatics Visualization, 2018)
NComputing Technology is becoming increasingly important and is being used both in academe and business industry because of its capability of saving energy and maintenance costs. However, the adoption of this technology faces with concerns particularly in end users experiences. The paper aimed to examine the collection of some of the issues and challenges facing the NComputing technology adoption in academe particularly in Surigao del Sur State University and offered an initial roadmap to view the challenges and problems for further research. Findings revealed that most of the students were not satisfied with the performance of this technology. But, for technical support, they found it easy to maintain and troubleshoot.